Both alpha(1)- and alpha(2)-adrenoceptors in the Insular Cortex Are Involved in the Cardiovascular Responses to Acute Restraint Stress in Rats - Alves, Fernando H. F.; Crestani, Carlos Cesar [UNESP]; Resstel, Leonardo B. M.; Correa, Fernando M. A. (Public Library Science, 2014)
The insular cortex (IC) is a limbic structure involved in cardiovascular responses observed during aversive threats. However, the specific neurotransmitter mediating IC control of cardiovascular adjustments to stress is yet unknown. Therefore, in the present study we investigated the role of local IC adrenoceptors in the cardiovascular responses elicited by acute restraint stress in rats. Bilateral microinjection of different doses (0.3, 5, 10 and 15 nmol/100 nl) of the selective alpha(1)-adrenoceptor antagonist WB4101 into the IC reduced both the arterial pressure and heart rate increases elicited by restraint stress. However, local IC treatment with different doses (0.3, 5, 10 and 15 nmol/100 nl) of the selective alpha(2)-adrenoceptor antagonist RX821002 reduced restraint-evoked tachycardia without affecting the pressor response. The present findings are the first direct evidence showing the involvement of IC adrenoceptors in cardiovascular adjustments observed during aversive threats. Our findings indicate that IC noradrenergic neurotransmission acting through activation of both alpha(1)- and alpha(2)-adrenoceptors has a facilitatory influence on pressor response to acute restraint stress. Moreover, IC alpha(1)-adrenoceptors also play a facilitatory role on restraint-evoked tachycardiac response.